Employee motivation strategy of Rupali Bank Limited: a study on Ramna Corporate Branch - Jahan, Rafiqua Sifat (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2023.